Promoting Lifelong Physical Activity through Physical Education: A Review of Longitudinal Studies - Aarif Majeed; Khushdeep Singh; Mandeep Singh (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
Staying active is crucial for maintaining good health, feeling happy and enjoying life to the fullest. But research keeps showing us that people tend to become much less active once they finish their teenage years. School physical education lessons can really help young people develop a lasting love for exercise. This review brings together findings from various studies that look at how school sports affect people's exercise habits over the years and what role physical education plays in encouraging healthy lifestyles. Physical activity generally declines from childhood through adolescence, with modest stabilization or recovery in some individuals during adulthood. But when physical education programmes are done well focusing on building skills, creating a positive atmosphere and offering lots of fun activities they can really make a difference in whether someone stays interested in sport long term. Physical education helps people remain active throughout their lives by boosting their movement abilities, making them more willing to join in, building their confidence that they can succeed and helping them feel good when they exercise. All of these factors lead to greater independence and keep people exercising even after they leave school. It's worth noting that physical education works best when it's part of a bigger school wide approach and when it's backed up by local community programmes. Even though the results look promising, the current research has some real weaknesses like relying on people to report their own behavior, using different ways to measure things, and having different approaches across various cultures and schools. Future long-term studies need to focus on looking at how strong and thorough evidence actually affects outcomes. To sum up, physical education is a vital but often undervalued way of encouraging regular exercise and good health. When physical activity is sustained and high quality, it builds lifelong habits, skills and attitudes that support a healthy and more active way of living.